1998
DOI: 10.1063/1.368556
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of microwave magnetic envelope solitons in thin ferrite films through the nonlinear Schrödinger equation

Abstract: A theoretical analysis of microwave magnetic envelope soliton profiles and the soliton peak power response for high power magnetostatic wave ͑MSW͒ excitations in yttrium iron garnet ͑YIG͒ thin films has been made. This analysis was based on the standard nonlinear Schrödinger equation with all key parameters based on experiment. The measurements were done for magnetostatic backward volume waves in a 10.2 m YIG film, with a band edge at 5.06-5.07 GHz and operating point frequencies from 4.80 to 5.00 GHz. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…These values are right at the high end of the 0.01-0.10 range that is typical for MME solitons. 14 The ͉u͉ values for multi-peaked solitons should be at the high end of this range, of course, because the higher powers are needed to produce MPS pulses in the first place.…”
Section: Theoretical Connectionsmentioning
confidence: 98%
“…These values are right at the high end of the 0.01-0.10 range that is typical for MME solitons. 14 The ͉u͉ values for multi-peaked solitons should be at the high end of this range, of course, because the higher powers are needed to produce MPS pulses in the first place.…”
Section: Theoretical Connectionsmentioning
confidence: 98%
“…It may be noteworthy that this match is obtained without the inclusion of damping in the model. The NLS equation with damping included has been shown to provide an accurate model for bright MME solitons in YIG films [16].…”
mentioning
confidence: 99%
“…1,2 This technique provides an excellent method to experimentally test models of soliton formation and propagation in these systems. In particular, numerous past experiments [3][4][5] have indicated that the standard one-dimensional ͑1D͒ nonlinear Schrödinger ͑NLS͒ model gives an adequate description of soliton propagation in YIG films. In order for the 1D NLS model to be applicable, the following conditions are usually satisfied in experiments: first, the width of the film must be much less than the film length with typical film dimensions of 2ϫ15 mm 2 , and second, the input transducer must extend across the film width.…”
Section: Department Of Environmental Sciences University Of Montana/mentioning
confidence: 99%